Development and calibration of biochemical models for testing dental restorations. (June 2020) - Zhang, Anqi; Chen, Ruoqiong; Aregawi, Wondwosen; He, Yiting; Wang, Shuting; Aparicio, Conrado; Rudney, Joel; Chew, Hooi Pin; Fok, Alex S.
Abstract: Currently, resin composites are the most popular materials for dental restoration in clinical practice. Although the properties of such materials have been improved significantly, together with better clinical techniques used for their placement, early restoration failure still occurs too frequently. As clinical studies take years to complete, and new resin composites are being produced at ever increasing pace, laboratory assessment using accelerated but representative tests is necessary. The main types of failure in resin-composite restoration are tooth/restoration fracture and secondary caries, which are caused by a combination of mechanical and biochemical challenges. In this study, a biofilm model ( S. mutans ) and a chemical model (lactic-acid buffer) for producing artificial caries in bovine dentin are developed and calibrated against in situ data. Using a power law relationship between the demineralization depth and challenge duration, scale factors that convert the in vitro durations to the equivalent clinical durations are determined for different pH values for each model. The scale factors will allow the synchronization of biochemical and mechanical challenges in terms of their rates of action to potentially test resin-composite restoration in an accelerated but clinically representative manner. Statement of significance: Although the properties of resin composites for dental restoration have been improved significantly, early restoration failure still occurs too frequently. As clinical studies take years to complete, accelerated laboratory testing is necessary. Resin-composite restoration fail mainly through fracture and secondary caries, caused by a combination of mechanical and biochemical challenges. In this study, a biofilm and a chemical model for producing artificial caries in bovine dentin are calibrated against in situ data. Using a power law relationship between demineralization depth and challenge duration, scale factors are determined for different pH for each model. The scale factors will allow the synchronization of biochemical and mechanical challenges in testing resin-composite restoration in an accelerated but clinically representative manner. Graphical abstract: Image, graphical abstract